SISRUTE dan Tantangan Digitalisasi Kesehatan di Daerah: Tinjauan Hukum terhadap Keadilan Akses Pelayanan Kesehatan - Febri Juhamsyah; Marice Simarmata (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The implementation of digitalization in the healthcare sector through the Integrated Referral sistem (Sistem Informasi Rujukan Terintegrasi/SISRUTE) offers significant opportunities to expand access and improve the quality of healthcare services, especially in remote and underserved areas of Indonesia. This paper aims to analyze the challenges of implementing SISRUTE from a legal perspective, focusing on the principle of equitable healthcare access. The study uses a normative juridical approach combined with literature analysis, examining national regulations, including Law No. 17 of 2023 on Health, Government Regulation No. 47 of 2021 on Hospital Administration, and supporting ministerial policies. The research identifies several barriers that hinder the effectiveness of SISRUTE implementation, such as uneven distribution of digital infrastructure, limited internet connectivity, lack of adequately trained healthcare personnel, and the absence of supporting local regulations that align with national policy frameworks. These challenges create disparities in the utilization of SISRUTE, particularly in rural and remote areas, undermining the constitutional mandate for equal access to health services. From a legal standpoint, the principle of equity in healthcare has yet to be fully realized through SISRUTE due to these systemic gaps. The study concludes that strategic efforts are needed to improve intergovernmental coordination, harmonize health and digital regulations, strengthen healthcare workers' digital competencies, and invest in robust infrastructure development. Only through an integrated legal, technological, and human resource approach can SISRUTE fulfill its intended function in supporting a fair, inclusive, and effective healthcare referral system nationwide. This paper contributes to ongoing discourse on legal reforms for digital health equity in Indonesia.